1998
DOI: 10.1183/09031936.98.11051021
|View full text |Cite
|
Sign up to set email alerts
|

Asbestosis, pleural plaques and diffuse pleural thickening: three distinct benign responses to asbestos exposure

Abstract: The aim of this study was to investigate by computed tomography (CT) whether asbestosis, diffuse pleural thickening and/or pleural plaques are statistically associated. We also tried to find criteria to differentiate between diffuse and circumscribed pleural thickening. From 231 exposed workers, only those subjects whose radiograph showed neither bilateral calcified pleural plaques nor small pulmonary opacities higher than 1/1 grade according to the 1980 International Labour Office (ILO) Classification were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 41 publications
4
72
0
4
Order By: Relevance
“…Care must be taken to distinguish pleural plaques from other pleural abnormalities, such as diffuse pleural thickening [DPT] (Copley et al, 2001;Gevenois et al, 1998;Jeebun & Stenton, 2012;McLoud et al, 1985;Miles et al, 2008) or asbestosis, which have substantially different biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Care must be taken to distinguish pleural plaques from other pleural abnormalities, such as diffuse pleural thickening [DPT] (Copley et al, 2001;Gevenois et al, 1998;Jeebun & Stenton, 2012;McLoud et al, 1985;Miles et al, 2008) or asbestosis, which have substantially different biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a study which included 551 chest radiographs reinterpreted by six independent consultants in chest radiology, Gitlin et al (14) concluded that the difference between interpretations by initial readers and reinterpretations was too great to be attributed to interobserver variability. It has to be stressed, however, that in most cases the reinterpretations of small opacity profusions were more accurate than those reported by initial readers (14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 65%
“…High-resolution computed tomography (HRCT) has proved to be a simple, reliable, and reproducible method for classifying lung fi brosis and diagnosing asbestosis, and it would be possible to use it as a part of an international classifi cation (11,12). Gamsu found that high-resolution CT scans had a higher detection rate for interstitial fi brosis than chest radiographs classified according to the ILO classification in occupationally exposed population (6).…”
mentioning
confidence: 99%
“…The presence of fibrohyaline plaques (areas of hard whitish fibrous tissue, with well-defined borders, sometimes with pearl-like nodules) ( Figure 4) indicates a previous asbestos exposure, and is often associated with MPM (23,24).…”
Section: Thoracoscopic Findingsmentioning
confidence: 99%
“…The second priority is a good knowledge of the macroscopic normal appearance of the pleura and of its pathological processes, in order to clearly identify inflammatory or neoplastic lesions, irrespective of their origin (23,24).…”
Section: Thoracoscopic Findingsmentioning
confidence: 99%